Pengelolaan Evaluasi Pembelajaran Kurikulum 2013 di SDIT Gunung Jati - Ina Magdalena; Liana Irma Susanti; Siti Rahmawati (Jurnal Halaqah, 2020)
This study aims to describe the management of the 2013 curriculum learning evaluation. Types of qualitative research. Research site at SDIT Gunung Jati. Teacher research subjects and fourth-grade students at SDIT Gunung Jati. Interview data collection techniques. Research subjects are teachers who teach the curriculum. Data collection is done through interviews. The steps of data analysis are recording and collecting, reducing, presenting, and verifying. The results of this study indicate those positive teacher perceptions because teachers carry out evaluations well as evidenced by teachers applying authentic assessments in learning which include assessments of affective, cognitive, and psychomotor aspects.